Analysis of Financial Performance: 7ELEVEN SDN. BHD - Daisy Mui Hung Kee; Nur Shaidah binti Juseef; Nur Nabilah binti Abdul Halim; Nur Nafisah binti Mohd Razi; Nur Sorfina binti Shamsuddin (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2021)
7ELEVEN (7 eleven) is well-known franchise in the world as in Malaysia. The purpose of this study is to analyse the financial performance of 7 eleven for two consecutive years, 2019 and 2020. The comparison of this performance is required to track their achievement on stability, liquidity, profitability and on maintaining their market share. The qualitative data based on survey and quantitative data in the annual report needed to make the comparison of the financial performance. The ratios used to analyse the company financial performance are market value ratios, profitability ratios, efficiency ratios and liquidity ratios. The result from the survey contributed the information on how society preferred go to the 7 eleven and the result from the ratios showed the financial performance of the company. The financial performance report will be the summary of the financial health of the company helping various investors and stakeholders to take investment decision.